2014
DOI: 10.1002/cpt.11
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Interleukin Therapy in Asthma

Abstract: Asthma remains one of the most prevalent and costly diseases in the United States. Asthma accounts for a significant amount of direct medical expenditures and indirect cost from days lost at school and work. Modern understanding of its complex pathogenesis has allowed recognition of the heterogeneity of the disease across populations and the various inflammatory pathways that drive airway inflammation in asthma. Interleukins play important roles in both eosinophilic and noneosinophilic asthma, and anti-interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 89 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…Chronic inflammatory changes in lungs lead to asthma. Modern understanding of its complex pathogenesis has allowed recognition of the heterogeneity of the disease across populations and the various inflammatory pathways that drive airway inflammation in asthma . Recent studies have shown that interleukins (IL‐4, IL‐5 and IL‐13) play important roles in both eosinophilic and non‐eosinophilic asthma .…”
Section: Diseases Associated With Chronic Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammatory changes in lungs lead to asthma. Modern understanding of its complex pathogenesis has allowed recognition of the heterogeneity of the disease across populations and the various inflammatory pathways that drive airway inflammation in asthma . Recent studies have shown that interleukins (IL‐4, IL‐5 and IL‐13) play important roles in both eosinophilic and non‐eosinophilic asthma .…”
Section: Diseases Associated With Chronic Inflammatory Responsementioning
confidence: 99%
“…Modern understanding of its complex pathogenesis has allowed recognition of the heterogeneity of the disease across populations and the various inflammatory pathways that drive airway inflammation in asthma . Recent studies have shown that interleukins (IL‐4, IL‐5 and IL‐13) play important roles in both eosinophilic and non‐eosinophilic asthma . It is also observed that IL‐6 levels are elevated in the lung epithelial cells of asthmatic patients compared with healthy controls .…”
Section: Diseases Associated With Chronic Inflammatory Responsementioning
confidence: 99%
“…As an important signal molecule, IL-4 can exacerbate airway inflammation through modulating eosinophils, lymphocytes, and air epithelial cells that play an important role in the pathogenesis of asthma. [6,7] IL-4 is reported to play a pivotal role in phenotypic or functional changes of bronchial asthma, such as airway hyperresponsiveness, eosinophil infiltration, and mucus overproduction, [8] while IL-6 is a small-size glycoprotein (21 kDa) that acts on epithelial and immune cells and is produced by cells from innate immune system, including macrophages, dendritic cells, mast cells, and neutrophils. Previous studies show that IL-6 can lead to asthma and other lung diseases via increasing airway mucus hypersecretion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, IL-4 is reported to play a pivotal role in phenotypic or functional changes of bronchial asthma, such as airway hyperresponsiveness, eosinophil infiltration, and mucus overproduction [24].…”
Section: Discussionmentioning
confidence: 99%